Effect of steel fiber on the crack permeability evolution and crack surface topography of concrete subjected to freeze-thaw damage - Zeng, Wei (2020)
This paper describes the steel fiber effect on the crack permeability and crack surface topography of concrete subjected to freeze-thaw damage. The sequential crack permeability of steel fiber reinforced concrete are investigated by a vacuum permeability set-up. The topographical analysis is applied on the crack surface by an invented 3-D laser scanning equipment. The results show that the crack permeability of concrete is less than the value predicted by the Poiseuille flow model and their difference decreases gradually with the crack widening. With increment of steel fiber dosage and freeze-thaw damage level, the effect of steel fiber on reducing the crack permeability becomes strong. Topographical analysis illustrates that both steel fiber and freeze-thaw damage enhance the roughness of concrete crack surface. The relationship between roughness number of crack surface and material permeability parameter α follows an exponential function, which can be employed to quickly estimate the crack permeability of concrete.